PENGARUH SIKAP, KESADARAN WAJIB PAJAK DAN PENGETAHUAN PERPAJAKAN PADA KEPATUHAN MEMBAYAR PAJAK BUMI DAN BANGUNAN - Budhiartama, I Gede Prayuda; Jati, I Ketut (E-Jurnal Akuntansi, 2016)
This study aims to determine the Influence Attitudes, Awareness and Knowledge Taxpayer Compliance land and building at taxpayer pays tax on land and buildings in the city of Denpasar. A sample size of 132. 743 taxpayer in 2014 as the population was determined using the formula Slovin with a sample size of 100 respondents with characteristics, namely: Gender, age, and education level. Data analysis method is multiple linear regression analysis. Based on the calculation results of multiple linear regression showed that the perception of taxpayers about the attitudes, awareness and knowledge of taxpayers taxpayer positive and significant effect on tax compliance from evading taxes on the Denpasar Revenue Service
Keywords: attitude, awareness, knowledge and compliance